Teacher Digital Literacy and Instructional Innovation in Southeast Asia: Comparative Insights from Global Educational Systems - Mariana, Rina Rifqie; Nurjanah, Nunung (Yayasan Sinergi Kawula Muda, 2023)
This narrative review explores the critical role of teacher digital literacy in shaping effective pedagogy and student engagement within 21st-century education. The study aims to synthesize empirical findings and global perspectives on the development, challenges, and implications of digital competence among educators. Using a systematic literature analysis, sources were drawn from Scopus, Google Scholar, ERIC, and related databases, focusing on studies from 2019 to 2024. Keywords included teacher digital literacy, ICT in education, and technology integration. The review identifies significant associations between teachers’ digital skills and their ability to adopt innovative, student-centered teaching methods. It further highlights challenges such as infrastructural deficits, inconsistent training, and policy limitations, especially in socioeconomically disadvantaged and geographically remote settings. Comparative analysis reveals that nations with structured professional development and supportive policies show higher digital competence and better learning outcomes. Best practices include collaborative learning communities, curriculum integration frameworks like TPACK, and sustained investment in educational infrastructure. The review concludes that developing teacher digital literacy requires coordinated policy, targeted funding, and culturally responsive training. These efforts are essential to address persistent digital divides and build equitable, inclusive educational systems capable of adapting to future technological demands.